A real‐world experience with the bioactive human split thickness skin allograft for venous leg ulcers. Issue 4 (19th May 2020) - Kirsner, Robert S.; Margolis, David; Masturzo, Arti; Bakewell, Katie
Abstract: Data collected from standardized clinical practices can be valuable in evaluating the real‐world therapeutic benefit of skin substitutes in the treatment of venous leg ulcers (VLU). Utilizing such a dataset, this study aimed to validate the effectiveness of a bioactive human split‐thickness skin allograft for the treatment of VLU in the real‐world setting and to understand how certain variables impacted healing rates. From a pool of 1474 VLU treated with allograft, 862 ulcers in 742 patients were selected from a large wound EMR database and analyzed. All patients received standard wound care prior to allograft application. Impact of ulcer duration, number of applications, ulcer size, and time to application were analyzed. The VLU, on average, were of 189 days duration with a mean ulcer size of 19.3 cm 2 . During treatment, 70.7% of wounds healed, with an average time to closure of 15 weeks (SD = 14.1 weeks). The percentage of VLU less than one‐year duration that healed was significantly higher (72.3%) than the percentage of VLU with duration of greater than 1 years (51.5%) ( χ 2 = 18.17; P < .001). Ulcers less than 10 cm 2 in size were more likely to heal (73.9%) than those larger than 10 cm 2 (67.9%) ( χ 2 = 8.65, P = .03). VLU receiving allograft within 90 days of initial presentation are 1.4 times more likely to heal vs those receiving their first BSA application after 90 days of standard of care (95% CI: [1.05, 1.86], P = .02). Allograft used in wound clinics healed a majority of refractory VLU, even in large ulcers of long duration, which are more difficult to heal. Smaller wound, size, and shorter wound duration were associated with greater likelihood of healing. VLUs treated earlier with allograft had better healing outcomes. Clinicians may consider more aggressive and timely treatment with allograft for refractory VLU.